Nitrogen inclusion in carbon nanotubes initiated by boron doping and chlorination: Their use as electrocatalysts for oxygen reduction reaction - Maboya, Winny K.; Maubane-Nkadimeng, Manoko S.; Jijana, Abongile N.; Mmako, Herry K. (Frontiers in Materials, 2022)
Use of carbon nanostructures doped with heteroatoms as electrocatalysts for oxygen reduction reaction (ORR) has attracted intense research in recent years because they are highly conductive, have good durability and are highly electroactive. Doping of carbon nanomaterials (CNMs) with boron (B) and nitrogen (N) is one of the strategies used to modify their characteristics. The influence of B doping on the synthesis of CNMs has not been extensively studied and is not well understood, as compared to N doping studies. In this study, B and N co-doped carbon nanotubes (CNTs) were successfully synthesized via chlorination and decomposition of triphenyl borane in a two-zone catalytic vapor deposition (CVD) reactor. N-doping resulted from the use of nitrogen as carrier gas. Microscopic, and spectroscopic techniques revealed that in addition to B doping, N bonding with carbon nanostructures together with the presence of defects, played pivotal roles in determining the extent of ORR performance of the produced CNMs. Introduction of N in the carbon matrix during B doping resulted in reduction of the amount of B doped into the matrix, due to competitive incorporation of N which inhibited B introduction. The presence of pyridinic N species was responsible for a 2e- ORR performance.